Trypanosoma congolense: Tissue distribution of long-term T- and B-cell responses in cattle - Lutje, V.; Taylor, K.A.; Boulange, A.F.; Authié, Edith (Elsevier, 1995)
Memory T- and B-cell responses to trypanosome antigens were measured in peripheral blood mononuclear cells, spleen and lymph node cells obtained from 4 trypanotolerant N'Dama cattle which had been exposed to 6 experimental infections with Trypanosoma congolense. These cattle were treated with trypanocidal drugs following each infection and had remained aparasitaemic for 3 years prior to this study. The antigens used were whole trypanosome lysate, variable surface glycoprotein, a 33thin000 MW cysteine protease (congopain) and a 70thin000 MW heat-shock protein. As parameters of T-cell-mediated immunity, T-cell proliferation and IFN-gamma production were monitored. Lymph node cells, spleen cells and peripheral blood mononuclear cells all proliferation to a mitogenic stimulus (concanavalin A) but only lymph node cells responded to trypanosome antigens. Similarly, IFN-gamma was produced by both lymph node and spleen cells stimulated with concanavalin A but only by lymph node cells stimulated with variable surface glycoprotein and whole trypanosome lysate. T. congolense-specific antibodies were detected in sera and in supernatants of cultured lymph node and spleen cells after in vitro stimulation with lipopolysaccharide and recombinant bovine interleukin-2. It is concluded that memory T- and B-cell responses are detectable in various lymphoid organs in cattle 3 years after infection with T. congolense.